Guest Editorial, Themed Section - Cheri Fernandez (Grounded Theory Review: An International Journal)
When grounded theory first emerged as a research methodology (Glaser, 1965; Glaser & Strauss, 1967) it literally rocked the research world and was quickly adopted by disciplines other than sociology from which it derived. For the first decade or two grounded theory continued without much ‘disturbance.’ However, later graduate students took up the public ‘challenge’ to “take the method in any direction they wished” (Glaser, 1978, p.158). First on the scene was the qualitative method by Strauss and Corbin, first known as qualitative data analysis but now called Straussian grounded theory.